Organic Farming Sharpens Plant Defenses in the Field - Krey, Karol L.; Nabity, Paul D.; Blubaugh, Carmen K.; Fu, Zhen; Van Leuven, James T.; Reganold, John P.; Berim, Anna; Gang, David R.; Jensen, Andrew S.; Snyder, William E. (Frontiers in Sustainable Food Systems, 2020)
Plants deploy a variety of chemical and physical defenses to protect themselves against herbivores and pathogens. Organic farming seeks to enhance these responses by improving soil quality, ultimately altering bottom up regulation of plant defenses. While laboratory studies suggest this approach is effective, it remains unclear whether organic agriculture encourages more-active plant defenses under real-world conditions. Working on the farms of cooperating growers, we examined gene expression in the leaves of two potato (Solanum tuberosum) varieties, grown on organic vs. conventional farms. For one variety, Norkotah, we found significantly heightened initiation of genes associated with plant-defense pathways in plants grown in organic vs. conventional fields. Organic Norkotah fields exhibited lower levels of nitrate in soil and of nitrogen in plant foliage, alongside differences in communities of soil bacteria, suggesting possible links between soil management and observed differences in plant defenses. Additionally, numbers of predatory and phloem-feeding insects were higher in organic than conventional fields. A second potato variety, Alturas, which is generally grown using fewer inputs and in poorer-quality soils, exhibited lower overall herbivore and predator numbers, few differences in soil ecology, and no differences in gene-activity in organic and conventional farming systems. Altogether, our results suggest that organic farming has the potential to increase plants' resistance to herbivores, possibly facilitating reduced need for insecticide applications. These benefits appear to be mediated by plant variety and/or farming context.